Teachers’ Technique in Teaching Speaking in SMAN 1 Kinali Academic Year 2021/2022 - Yunita, Andini; Kardena, Absharini; Roza, Veni; Irwandi, Irwandi (ALSYS, 2023)
The purpose of this study was to find out the teachers’ technique in teaching speaking and how did the teacher apply during the classroom at SMAN 1 Kinali Academic Year 2021/2022. Researcher found problems related to teacher and students. The first problem was that teacher used the same variety technique to teach speaking in class. Second problem was the students become surfeited in the classroom. The third problem was controlling the class with several students’ character. From the phenomenon above, the researcher wanted to analyze what types of teachers’ technique in teaching speaking and how to apply the technique in teaching speaking.This research was qualitative descriptive study. Researcher conducted this research at SMAN 1 Kinali. The informant of this research was the English teacher SMAN 1 Kinali. Data collection techniques used in this study were interviews and observations checklist. Based on the findings of this study, it was found that there were four types of techniques of teaching speaking, namely: Pair and group technique, Drilling technique, Jigsaw technique, Simulation technique. In learning process during speaking material, the teacher used the same technique and students became surfeite in learning so it was necessary to know what were the techniques that used by the teacher in the learning process. The teacher has implemented principles of techniques in teaching speaking and how to apply teaching speaking at SMAN 1 Kinali. The techniques that used by the teacher was effective and motivating students. The researcher also found out why the teacher used variety techniques in teaching speaking to make students fluent, become active and build their self-confidence, and to master speaking skill as well. By using techniques in teaching speaking, it motivated students to speak and to help students improving their speaking ability.